1992
DOI: 10.1029/91ja02608
|View full text |Cite
|
Sign up to set email alerts
|

On the possibility of auroral remote sensing with the Viking ultraviolet imager

Abstract: An investigation was carried out to assess the value of ultraviolet auroral images for remote sensing of electron precipitation. We compared auroral images, obtained by both cameras of the Viking Ultraviolet Imager during April and early May 1986, with simultaneous measurements of electron precipitation from the DMSP F7 and HiLat satellites at low altitudes above the auroral zone. The camera signals in the pixels that viewed the low‐altitude satellite footprint were corrected for various instrumental and nonau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The goal of remotely sensing the mean energy and flux of the precipitating particles, which motivated the choice of a dual-camera system, has not been fully met, however. In a previous work [Steele et al, 1992, referred to hereinafter as paper 1] we showed that the total energy deposition can be estimated from the imager signal, with roughly 50% uncertainty. However, we also showed that the mean precipitating electron energy cannot be inferred from Viking two-camera image signal ratios, because the experimentally measured effective sensitivities of both cameras (i.e., the camera signals per unit precipitating electron energy flux over the viewed region of the atmosphere) vary similarly with the mean electron energy.…”
Section: Introductionmentioning
confidence: 96%
“…The goal of remotely sensing the mean energy and flux of the precipitating particles, which motivated the choice of a dual-camera system, has not been fully met, however. In a previous work [Steele et al, 1992, referred to hereinafter as paper 1] we showed that the total energy deposition can be estimated from the imager signal, with roughly 50% uncertainty. However, we also showed that the mean precipitating electron energy cannot be inferred from Viking two-camera image signal ratios, because the experimentally measured effective sensitivities of both cameras (i.e., the camera signals per unit precipitating electron energy flux over the viewed region of the atmosphere) vary similarly with the mean electron energy.…”
Section: Introductionmentioning
confidence: 96%
“…Instead of quenching mechanisms, the FUV technique relied on absorption of 02 at lower altitudes to supply an energy dependence. The potential of using FUV emissions from the Viking satellite as remote measures of characteristic energy was examined by Steele et al [1992]. They found only a weak dependence on energy, but they were only able to examine energies below 1.4 keV.…”
mentioning
confidence: 99%